'Just a Bit of Fun': How Recreational is Direct-to-Customer Genetic Testing?. Issue 1 (May 2015) - Felzmann, Heike
<x content-type="archive" xml:space="preserve">Abstract</x> Direct to consumer (DTC) genetic testing has given rise to much controversy, especially in relation to testing for health diagnostic purposes. This paper will consider whether consumers' use of DTC genetic testing should be understood as predominantly recreational. It will be argued that recreational testing can encompass all information domains, including most kinds of predictive health risk information. In relation to recreational testing the potential identity implications for the consumer become a significant concern, more so than the risks more traditionally associated with genetic testing. It will be concluded that while the DTC genetic testing sector is beset by numerous problems and an increase in consumers' genetic literacy is highly desirable, consumers' engagement with DTC genetic testing may be less problematic than sometimes assumed.